Recordkeeping for Texas - Schultheis, Robert A. (Thomson Learning, 2004)
Texas Recordkeeping gives a broad knowledge of business operations and the basic skills needed to keep better financial records. The text contains a colorful graphic design, new enrichment activities, and a new Recordkeeping for Texas supplement. Features, such as multicultural insights and interviews with individuals who use record keeping in their daily lives, capture students' interest